Disentangling the direct and indirect effects of agricultural runoff on freshwater ecosystems subject to global warming: A microcosm study - Allen, Joey; Gross, Elisabeth M.; Courcoul, Camille; Bouletreau, Stéphanie; Compin, Arthur; Elger, Arnaud; Ferriol, Jessica; Hilt, Sabine; Jassey, Vincent E.J.; Laviale, Martin; Polst, Bastian H.; Schmitt-Jansen, Mechthild; et al. (Water research (Oxford), 2021)
•Assessment of agricultural run-off (ARO) and global warming in aquatic microcosms•Direct ARO effects were higher phytoplankton biomass and lower grazer growth•Biotic interactions reversed the direct effect of ARO on phytoplankton•ARO effects were enhanced with multiple pulses compared to a single addition•Warming had no major effect on primary producers, consumers or their interactions Aquatic ecosystems are exposed to multiple stressors such as agricultural run-off (ARO) and climate-change related increase of temperature. We aimed to determine how ARO and the frequency of its input can affect shallow lake ecosystems through direct and indirect effects on primary producers and primary consumers, and whether warming can mitigate or reinforce the impact of ARO. We performed a set of microcosm experiments simulating ARO using a cocktail of three organic pesticides (terbuthylazine, tebuconazole, pirimicarb), copper and nitrate. Two experiments were performed to determine the direct effect of ARO on primary producers (submerged macrophytes, periphyton and phytoplankton) and on the grazing snail Lymnaea stagnalis, respectively. Three different ARO concentrations added as single doses or as multiple pulses at two different temperatures (22°C and 26°C) were applied. In a third experiment, primary producers and consumers were exposed together to allow trophic interactions. When functional groups were exposed alone, ARO had a direct positive effect on phytoplankton and a strong negative effect on L. stagnalis. When exposed together, primary producer responses were contrasting, as the negative effect of ARO on grazers led to an indirect positive effect on periphyton. Periphyton in turn exerted a strong control on phytoplankton, leading to an indirect negative effect of ARO on phytoplankton. Macrophytes showed little response to the stressors. Multiple pulse exposure increased the effect of ARO on L. stagnalis and periphyton when compared with the same quantity of ARO added as a single dose. The increase in temperature had only limited effects. Our results highlight the importance of indirect effects of stressors, here mediated by grazers and periphyton, and the frequency of the ARO input in aquatic ecosystems. [Display omitted]